1998
DOI: 10.1056/nejm199809033391006
|View full text |Cite
|
Sign up to set email alerts
|

Use and Cost Effectiveness of Smoking-Cessation Services under Four Insurance Plans in a Health Maintenance Organization

Abstract: Use of smoking-cessation services varies according to the extent of coverage, with the highest rates of use among smokers with full coverage. Although the rate of smoking cessation among the benefit users with full coverage was lower than the rates among users with plans requiring copayments, the effect on the overall prevalence of smoking was greater with full coverage than with the cost-sharing plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
244
1
14

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(265 citation statements)
references
References 22 publications
5
244
1
14
Order By: Relevance
“…In the study by Curry et al [19], although they showed that the rates of smoking cessation were lower in patients for whom treatment costs were completely met by employers, more patients could quit smoking because more smokers were able to access free treatment. Similarly, in our study, more patients could be treated in the free period and more patients could quit smoking, but smoking cessation rates after one year were found to be very low, in fact lower than that in the second period (10.5% vs. 18.2%).…”
Section: Discussionmentioning
confidence: 98%
“…In the study by Curry et al [19], although they showed that the rates of smoking cessation were lower in patients for whom treatment costs were completely met by employers, more patients could quit smoking because more smokers were able to access free treatment. Similarly, in our study, more patients could be treated in the free period and more patients could quit smoking, but smoking cessation rates after one year were found to be very low, in fact lower than that in the second period (10.5% vs. 18.2%).…”
Section: Discussionmentioning
confidence: 98%
“…Using data from two randomized pharmacogenetic trials of tobacco dependence treatment, we have estimated the potential effect on treatment costs and long-term survival of using genetic testing to choose between TN and bupropion for individual smokers. Our approach differs from the previous cost-effectiveness analyses of tobacco dependence treatment [30][31][32][33][34][35][36] in the following ways: (i) we consider Under all parameter combinations that we considered, non-tailored varenicline was the most effective (and expensive) admissible treatment. Bupropion was dominated only in the best-case scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Although others have investigated the cost-effectiveness of pharmacologic smoking-cessation interventions, [30][31][32][33][34][35][36][37] we are the first to include a pharmacogenetic tailoring arm in such an evaluation. These previous studies have suggested that pharmacotherapy is cost-effective compared to no treatment or counseling alone, with ICERs in the range of $800-$1200 per quitter and $900-$11 200 per LY, depending on the regimen and the age and sex of the smoker.…”
Section: Discussionmentioning
confidence: 99%
“…Effective smoking cessation programs have the potential to dramatically decrease health care utilization and costs [41][42][43][44]. A cost-benefit analysis found that the ratio of benefits to cost varies from US$0.80 to US$2.40 saved per dollar spent on smoking cessation programs, depending upon the type of intervention [45].…”
Section: Original Researchmentioning
confidence: 99%